ANALISIS KERUSAKAN JALAN RAYA PADA LAPIS PERMUKAAN DENGAN METODE PAVEMENT CONDITION INDEX (PCI) DAN METODE BINA MARGA RUAS JALAN LUKOK KUBANG PUTIH STA. 0 + 000 – STA. 2 + 200) - Rizaldo, Irvan; Priana, Surya Eka; Herista, Febrimen (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Highways are one of the land transportation facilities that have an important role in human life, especially for economic and socio-cultural growth to support national development. To facilitate the mobility of the community so that they can provide good service according to the capacity needed, if there is damage to the road, it will hinder community activities, causing accidents. The purpose of this study was to determine the types of damage and the pavement index value of the Sungai Pua Kubang Putih road, so that it could compare the condition values of the Pua Kubang Putih road section based on two predetermined methods. The method used is the PCI (Pavement Condition Index) method and the Bina Marga method. Assessment of road conditions in the PCI method is by ranking from a value of 0-100 while the Bina Marga method is based on the order of priority of the road with a value range of 0-7. The types of damage found on the 2.2 km Pua Kubang Putih River road included holes, cracked blocks, cracked crocodile skin, and patches. In the PCI method the average value obtained is 68.63 which is a good road condition. In the Bina Marga method, a priority order value of 6.4 is obtained, meaning that the road is under periodic maintenance. After comparing the results of the research on the condition of the Sungai Pua Kubang Putih road section with the two methods, it turned out that the results and values were almost the same, namely the condition of the road section was still in good condition but required maintenance so as not to worsen road conditions.